Biodiversity of Photobacterium spp. Isolated From Meats - Fuertes-Perez, Sandra; Hauschild, Philippa; Hilgarth, Maik; Vogel, Rudi F. (Frontiers in Microbiology, 2019)
Photobacteria are common psychrophilic bacteria found in marine environments. Recently, several studies revealed high numbers of Photobacterium (P.) spp. on packaged fresh meat. Their occurrence appears relevant for the spoilage of meat, since species of the genus are already known as potent fish spoilage organisms. Here we report on distribution, biodiversity and specific traits of P. carnosum (n = 31), P. phosphoreum (n = 24) and P. iliopiscarium (n = 3) strains from different foods. Biodiversity was assessed by genomic fingerprinting, diversity index analysis, growth dynamics, comparison of metabolic activities and antibiotic resistance. We observed a ubiquitous occurrence of the species on all common meats independent of packaging conditions and producer suggesting contamination during an established processing or packaging step. Regarding biodiversity, the three species differed clearly in their growth properties and metabolic characteristics, with P. phosphoreum growing the fastest and showing the strongest alkalization of the media. On strain level we also recorded variations in enzymatic reactions, acid production and antibiotic resistances not restricted to specific meat types. This depicts high biodiversity on species and strain level on each contaminated meat sample. Our analysis showed that meat-borne strains of P. phosphoreum and P. iliopiscarium clearly differed from their type strains from a marine habitat. Additionally, we report for the first time isolation of P. carnosum strains from packaged fish, which in contrast showed comparable phenotypic properties to meat-borne strains. This hints at different initial origins of P. phosphoreum/P. iliopiscarium (marine background) and P. carnosum (no demonstrated marine background) contaminations on fish and meat, respectively.